Review of thirty-one cases of salivary gland tumours in children and adolescents seen in a tertiary health care centre in Nigeria - Lawal, Ahmed; Adisa, Akinyele; Kolude, Bamidele; Adeyemi, Bukola (Journal of Stomatology, 2015)
Introduction. Salivary gland tumours (SGTs) are rare neoplasms. When compared to salivary gland inflammatory lesions, SGTs are relatively rare in children/adolescents with estimated annual incidence for all juvenile age groups of 1-2 tumours per 100,000 persons. This study reviewed SGTs in children/ adolescents seen at a reference tertiary hospital in Nigeria. Material and methods. This was a review of all SGTs in subjects aged 19 years and below from archival records of the University College Hospital Ibadan. All lesions were analysed for age, gender and site using SPSS for Windows (version 20.0; SPSS Inc. Chicago, IL). Inflammatory and non-neoplastic swellings were excluded from the study. Result. Out of a total of 413 SGTs that were diagnosed over the study period, 31 (7.5%) were seen in children/adolescents. The male:female ratio was 2.1:1. The mean age was 14.2 (±3.4) years (range = 6-19 years) and majority (93.5%) occurred at the age of 10 years and above. There were 19 benign cases (61.3%) while 12 (31.8%) were malignant. Pleomorphic adenoma in 16 (51.6%) cases was the most common lesion seen followed by mucoepidermoid carcinoma with 7 (22.6%) cases. Malignant SGTs in children occurred more often in the minor salivary glands (50.0%) compared with five (41.7%) cases that occurred in the parotid gland. Conclusion. This study showed that SGTs are relatively rare in children/adolescents and benign SGTs are more commonly seen than their malignant counterparts in this age group. SGTs were almost exclusively seen in children above the age of ten and no lesions were found in children younger than five years of age.